78 Leading transformation in a regional NHS tertiary referral service (the lateral skull base service in leeds). (3rd November 2019) - Verma, Sanjay; Deniz, Kenan
Abstract : Leeds provides a regional tertiary referral service for vestibular schwannoma (also known as acoustic neuroma) and other lateral skull base pathologies, receiving referrals from across West Yorkshire. Such were the increasing demands on the service, it was struggling to keep pace with the volume of new referrals and follow up of existing patients, leading to unacceptably high waiting times for clinic appointments and results. In March 2018 Mr Sanjay Verma assumed the position of Clinical Lead for the Lateral Skull Base service and led it through National Peer review. As a consequence of this several areas for improvement were identified. Mr Verma, and his neurosurgical Consultant colleague, Mr Kenan Deniz, devised an Action Plan, aimed at transforming the service, both to bring it in line with national guidelines and also to improve the quality of the service delivered to patients. Firstly, a system of virtual follow up was introduced for patients being managed conservatively with serial MRI scanning. This has significantly improved the patient experience by obviating the needs for many patients to travel long distances for follow up appointments. Secondly, Mr Verma and Mr Deniz engaged with Public Health physicians in a Better Value Healthcare project to determine the specific needs of the Lateral Skull base service, taking into account the perspectives of clinicians and patients. As a result of this, collaborative work was undertaken with Radiology colleagues to determine the optimal and safest imaging protocol for managing patients conservatively. Furthermore, a Lateral Skull Base Multidisciplinary Team discussion meeting and clinic were conceived and delivered, dramatically reducing patient waiting times for clinic appointments and results. This has culminated in the Lateral Skull Base service being awarded the 2019 Leads Teaching Hospitals 'Time to Shine' award for Improving Quality and Safety.